Bidirectional association between depression and cognition in Chinese middle-aged and older women: a 10-year longitudinal study - Jiang, Xiaoxu; Jiang, Zheng (Frontiers in Psychiatry, 2025)
BackgroundWomen’s health is an important issue worldwide, and as the population is aging, the health of middle-aged and older women is becoming increasingly vital. Although many studies have examined the relationship between cognition and depression, few studies have been conducted specifically with middle-aged and older women. This study used a longitudinal approach to examine the bidirectional relationship between cognition and depression in middle-aged and older women.MethodsThe study used three waves (2011, 2015, and 2020) of data from the China Health and Retirement Longitudinal Study (CHARLS), enrolling a total of 4,618 middle-aged and older women aged over 45 years. Participants’ general demographic characteristics were analyzed descriptively, and changes in study variables were measured using repeated-measures analysis of variance. Generalized estimating equation (GEE) and cross-lagged models were used to investigate the longitudinal relationship between depression and cognition.ResultsThe results of the GEE and cross-lagged models revealed that previous cognitive problems lead to future depression and prior depressive conditions affect subsequent cognition.ConclusionsThere is a bidirectional relationship between depression and cognition in middle-aged and older women over time. More clinical mechanisms need to be explored in the future.